Evaluation of an Automated Vaccination Strategy Against Aeromonas hydrophila in Grass Carp: A Comparative Study with Conventional Manual Injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Jian Zhao; Songming Zhu; Zhangying Ye (Fishes, 2026)
(1) Background: Vaccination is crucial for Ctenopharyngodon idella, yet the impact of delivery methods on welfare and immunity requires investigation. (2) Methods: This study compared manual (HI-V) and automated (AI-V) injections of inactivated Aeromonas hydrophila vaccine. (3) Results: Both methods induced protective immunity, with AI-V achieving a slightly higher Relative Percent Survival (41.67%) than HI-V (37.84%). AI-V promoted stable erythropoiesis and robust systemic/mucosal IgM responses with elevated HSP70 and IL-6. Conversely, HI-V triggered sharp transient stress and upregulated Gadd45γ, indicating greater genotoxic stress. (4) Conclusions: Automated injection offers comparable immune protection with reduced physiological stress and improved homeostasis, supporting its use for welfare-conscious aquaculture.